تعقيدات النظام الضريبي وأثرها على التهرب الضريبي -دراسة حالة الجزائر- - حيمران, محمد; بورنيسة, عبد النور (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة الى تحديد عناصر تعقيدات النظام الضريبي الجزائري وعلاقتهم بالتهرب الضريبي، ولهذا الغرض تم استخدام استبانة كأداة للبحث العلمي من خلال استقصاء عينة من الأكاديميين والمهنيين ذوي العلاقة بالمحاسبة والجباية، وتم معالجتها باستخدام البرنامج الاحصائي (SPSS.VER.26). وقد توصلت نتائج الدراسة الى ان النظام الضريبي معقد من حيث التشريع، اما من حيث الامتثال فهو منخفض التعقيد في الغالب مع كون بعض العناصر تتسم نوعا بالتعقيد. اما من حيث علاقة التعقيد الضريبي بالتهرب الضريبي فسواء كان التعقيد من حيث التشريع او الامتثال فكلاهما يؤثران على التهرب الضريبي الناتج من جانب المكلف، النظام الضريبي، الإدارة الضريبية، والاوضاع الاقتصادية. باستثناء علاقة التعقيدات الضريبية من حيث التشريع بالتهرب الضريبي الناتج عن الإدارة الضريبية التي لم نجد بينهما علاقة تأثير ذو دلالة إحصائية. This study aims to determine the elements of the complexities of the Algerian tax system and their relationship to tax evasion, and for this purpose a questionnaire was used as a tool for scientific research by surveying a sample of academics and professionals associated to accounting and taxation, using the statistical program (SPSS.VER.26). The results of the study found that the tax system is complex in terms of legislation, for compliance, it is of low complexity, with some elements being somewhat complex. Regarding the relationship of tax complexity to tax evasion, whether the in terms of legislation or compliance, both affect the tax evasion resulting from the taxpayer, tax system, tax administration, and economic conditions. With the exception of the relationship of tax complexity in terms of legislation and tax evasion resulting from tax administration, we did not find a statistically significant effect between them.
Keywords: الضرائب ; النظام الضريبي ; نظام التقدير الذاتي ; التعقيدات الضريبية ; التهرب الضريبي